Natural attenuation potential of downwelling streams for perfluorochemicals and other emerging contaminants - Hoehn, E (Water science and technology : a journal of the International Association on Water Pollution Research, 2007)
Stream augmentation with tertiary treated municipal wastewater-i.e., recycled water-is increasingly considered as an ecologically beneficial way to utilize recycled water, especially in semi-arid regions of the American Southwest. There is concern that emerging contaminants, i.e. unregulated but biologically active organic compounds, may be present in recycled water and will impact on the aquatic environment and the underlying groundwater. Emerging contaminants include a wide variety of chemically disparate compounds, including pharmaceuticals, endocrine disruptors, and residues of perfluorochemical surfactants (PFCs). This paper presents background data on the occurrence and transport of PFC in Upper Silver Creek (USC) and Coyote Creek, in San Jose, California. USC feeds into Coyote Creek, which discharges into San Francisco Bay. Augmenting the natural flow of Coyote Creek with highly treated recycled water is currently being considered as a means to provide more freshwater to the river ecosystem. The reach of interest is approximately 1,000 m where USC flows on alluvial fan deposits. Data indicate that some PFCs are refractory